Combination of capillary isoelectric focusing in a tapered capillary with MALDI-TOF MS for rapid and reliable identification of Dickeya species from plant samples - Horká, Marie; Salplachta, Jiří; Karásek, Pavel; Kubesová, Anna; Horký, Jaroslav; Matoušková, Hana; Slais, Karel; Roth, Michal (Analytical chemistry, 2013)
This study was undertaken to investigate feasibility of a combination of capillary isoelectric focusing (CIEF) in a tapered fused silica (FS) capillary with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) for a rapid and reliable identification of bacteria taken from plant-tissue-containing samples. Eight strains representing different species of the genus Dickeya were selected on the basis of close proximity of their isoelectric points: D. chrysanthemi, D. chrysanthemi bv. parthenii, D. chrysanthemi bv. chrysanthemi, D. dadantii, D. paradisiaca, D. solani, D. diffenbachiae, and D. dianthicola. Because the Dickeya species (spp.) cannot be easily discriminated from each other when CIEF is performed in a cylindrical FS capillary (commonly used in CIEF) even if a narrow pH gradient is used, a tapered FS capillary was employed instead, which enabled satisfactory discrimination of the examined bacteria due to enhanced separation efficiency of CIEF in the tapered FS capillary. CIEF in the tapered FS capillary was also successfully used for the detection and characterization of Dickeya spp. in a plant-tissue-containing sample. Then an off-line combination of CIEF with MALDI-TOF MS was employed for rapid and reliable identification of Dickeya spp. in the plant-tissue-containing sample. It was found that the presence of plant tissue did not affect the results, making the proposed procedure very promising with respect to the fast and reliable detection and identification of bacteria in plant-tissue-containing samples.
Keywords: elektroforéza kapilární; časové faktory; Plant Proteins; Plant Extracts; Time Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; isoelektrická fokusace; spektrometrie hmotnostní - ionizace laserem za účasti matrice; rostlinné proteiny; Isoelectric Focusing; rostlinné extrakty; Enterobacteriaceae; Electrophoresis, Capillary